2006
DOI: 10.4049/jimmunol.177.12.8531
|View full text |Cite
|
Sign up to set email alerts
|

Local and Systemic Effects of Intranodally Injected CpG-C Immunostimulatory-Oligodeoxyribonucleotides in Macaques

Abstract: Immunostimulatory CpG-C oligodeoxyribonucleotides (ISS-ODNs) represent a promising strategy to enhance vaccine efficacy. We have shown that the CpG-C ISS-ODN C274 stimulates macaque blood dendritic cells (DCs) and B cells and augments SIV-specific IFN-γ responses in vitro. To further explore the potential of C274 for future vaccine studies, we assessed the in vivo effects of locally administered C274 (in naive and healthy infected macaques). Costimulatory molecules were marginally increased on DCs and B cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 107 publications
(140 reference statements)
2
18
0
Order By: Relevance
“…with data from previous reports for macaque and human PBpDCs (2,22,48,49); this result also suggests that BM-pDCs, like PB-pDCs, express TLR-7 and TLR-9, the cognate receptors for single-stranded viral RNA and bacterial DNA with hypomethylated CpG motifs. It is interesting, however, that CD86 levels were consistently lower on BM-pDCs than on PB-pDCs in identically treated cultures.…”
Section: Vol 15 2008 Bone Marrow Plasmacytoid Dendritic Cells In Masupporting
confidence: 75%
“…with data from previous reports for macaque and human PBpDCs (2,22,48,49); this result also suggests that BM-pDCs, like PB-pDCs, express TLR-7 and TLR-9, the cognate receptors for single-stranded viral RNA and bacterial DNA with hypomethylated CpG motifs. It is interesting, however, that CD86 levels were consistently lower on BM-pDCs than on PB-pDCs in identically treated cultures.…”
Section: Vol 15 2008 Bone Marrow Plasmacytoid Dendritic Cells In Masupporting
confidence: 75%
“…Another possibility is that the small population of activated dendritic cells alters the properties of resident dendritic cells and other immune cells in lymph nodes. Previous results from Robbiani's group have indicated that single intranodal administration of C274 produced local and systemic effects on lymph node cell functions (45). In conclusion, the skin administration of immune regulatory molecules can induce a systemic antitumor immune response without targeting specific tumor-associated antigens.…”
Section: Discussionmentioning
confidence: 88%
“…In addition to inducing alpha interferon production from pDCs and enhancing antigen-presenting cell function, these microbial products also regulate memory B-cell homeostasis and antibody production (3,28,29). Studies in humans and in nonhuman primate models indicate that CpG ODN administration can enhance vaccine responsiveness (30,31,33).…”
Section: Discussionmentioning
confidence: 99%